General practitioner conduct of clinical services representing comprehensive geriatric assessment is associated with lower risk of mortality in older Australians receiving home care packages. (23rd December 2020) - Visvanathan, Renuka; Amare, Azmeraw T; Wesselingh, Steve; Inacio, Maria C
Abstract: Objectives: The purpose of this paper is to investigate the utilisation of general practice Medicare Benefit Schedule (MBS) services aligned to Comprehensive Geriatric Assessment (CGA) within 6 months of an aged care eligibility assessment and its effects on mortality and transition to permanent residential aged care (PRAC). Design: Retrospective cohort study from the Historical Cohort of the Registry of Senior Australians. Setting: Community. Participants: In total, 69, 171 Individuals (aged 75+) receiving home care packages (HCPs) between 2011 and 2015. Outcome measures: Mortality and transition to PRAC. Results: The claims for a management plan with team care arrangement (TCA) within 3 months of the health assessment (i.e. CGA) was present in 5% and associated with 14% lower mortality (adjusted hazard ratio [aHR], 95%CI = 0.86, 0.80–0.93) compared to no claims, lower than that seen with partial CGA which was either health assessment claims only 7.0% (aHR, 95%CI = 0.93, 0.89–0.97) or management plan coupled with TCA claims only 9.0% (aHR, 95%CI = 0.91, 0.89–0.97). This pattern was seen in those frailer but not in those where the frailty index score was <0.21. Claims for management plans coupled with TCAs alone were associated with a 10% lower transition to PRAC (asHR, 95%CI = 0.90, 0.85–0.96) in those with FI score < 0.21 while this estimate was not significant in individuals with FI score ≥ 0.21. Conclusion: It appears the conduct of a combination of interventions considered to be components of the CGA by GPs was associated with a lower risk of mortality that no claims or partial conduct of CGA.